Peer Interaction: A Compromise or a Necessity? - Katherine I. Kang (Studies in Applied Linguistics & TESOL, 2015)
In both research and practice, interaction with teachers or native speakers (NSs) has often been believed to play a facilitative role in second language (L2) development. However, as many learners in the classroom interact most frequently with other learners, there is a need to understand how peer interaction may differ from other types of interaction, such as learner-NS interaction, and how it may shape L2 development. Based on a review of studies on task-based peer interaction, this paper seeks to investigate its effect on L2 learning. The results indicate that peer interaction can benefit learners in various ways by creating opportunities to produce and modify output, receive feedback, and engage in collaborative dialogue. However, studies also found that having learners work together in itself does not automatically promote learning, and suggestions for creating more learning opportunities in peer interaction are discussed.